2016
DOI: 10.1016/j.foodhyd.2015.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Properties of partially denatured whey protein products: Formation and characterisation of structure

Abstract: a b s t r a c tPartially denatured whey protein (PDWPC) products have been manufactured using a controlled heating process that allows control of the degree of denaturation of the whey proteins. This is assessed by following the change in free sulphydryl content of the protein as heating progresses. This allows the formation of soluble whey protein aggregates of diverse particle size and morphology. The PDWPC's have been made using different manufacturing conditions (temperature, pH, degree of denaturation) to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 50 publications
0
20
0
Order By: Relevance
“…Extruded MPC80s had lower free sulfhydryl content than the control ( P < 0.05); melt temperature did not have a significant effect ( P > 0.05) (Table ). The free sulfhydryl concentration of E116 was numerically lower than E95 and E105, which suggested more protein denaturation and disulfide bond formation and/or free sulfhydryl oxidations at higher processing temperatures . SDS inclusion in the free sulfhydryl assay buffer did not affect ( P > 0.05) measureable free sulfhydryl concentration of the powders (Table ).…”
Section: Resultsmentioning
confidence: 94%
“…Extruded MPC80s had lower free sulfhydryl content than the control ( P < 0.05); melt temperature did not have a significant effect ( P > 0.05) (Table ). The free sulfhydryl concentration of E116 was numerically lower than E95 and E105, which suggested more protein denaturation and disulfide bond formation and/or free sulfhydryl oxidations at higher processing temperatures . SDS inclusion in the free sulfhydryl assay buffer did not affect ( P > 0.05) measureable free sulfhydryl concentration of the powders (Table ).…”
Section: Resultsmentioning
confidence: 94%
“…It is also possible that similar effects will be observed with thickening and gelation properties and work continues in this area. Our own work on controlling structure in WPC aggregates [6,7] has shown that control over solution viscosity can be achieved through controlled thermal aggregation so we are hopeful that similar effects can be achieved in the more complex binary aggregates of WPC and pectin. If this is achieved, it will open up the possibility of functional ingredients that can be more closely tailored to the functional requirements of a particular product or manufacturer.…”
Section: Resultsmentioning
confidence: 99%
“…[1][2][3] They have also been used to replace fats in foods due to their ability to mimic the sensory, optical, and rheaological properties of lipid droplets. [4,5] In view of this, there has been a growing interest in the fabrication of biopolymer microparticles made from proteins alone [6,7] or mixed protein and polysaccharide complexes. [3,[8][9][10][11][12][13] Molecular complexes form via interaction (commonly electrostatic) between two biopolymer molecules.…”
Section: Introductionmentioning
confidence: 99%
“…These include the protein type (molecular mass and amino acid composition) (6), protein hydrophobicity and free sulphydryl groups (7), protein concentration (8), the proportions of individual whey proteins in the mixture (9), the type and amount of salts (8,10,11), lipids (12), lactose (6), sucrose (13) present in the formula-tion, process conditions (pH, temperature, heating and cooling rate) (14,15), and/or specific treatments such as microparticulation of whey proteins (16)(17)(18). Among these factors, attention has been focused on protein concentration and pH.…”
Section: Introductionmentioning
confidence: 99%